A Woman with Tuberculous Meningitis (TBM) confirmed COVID-19 in the Intensive Care Unit: A Nursing Case Study - Lucky Pranianto (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2022)
Introduction. Patients with Tuberculous Meningitis (TBM) are at risk for opportunistic infections, one of which is infection by SARS-CoV-2. This condition can occur when patients with TB meningitis have a decreased immune system in addition to other causes of immunosuppression such as advanced age, socioeconomic status and malnutrition. TBM is a type of extrapulmonary tuberculosis that causes the most harmful and lead to disability and increasing mortality rate in more than half of cases. Case Presentation. A 35-year-old woman with TBM with COVID-19 infection showed conditions such as loss of consciousness, fever and headache. Patient’s Blood Gas Analysis shows hypocapnia where PaCO2 levels are 12 mmHg, with clinically patients experiencing bradypnea (respiratory rate = <12 x/min. Furthermore, patient got intubated and treated with a mechanical ventilator. After five days the use of a mechanical ventilator in the ICU isolation, patient showed improvement and extubating was carried out on the fifth day. Discussion. The condition of fever, headache and hypocapnia in patients with TBM can occur due to damage to the central nervous system. Patients experience hypocapnia after hyperventilation previous days ago and followed by decreasing CO2 levels. The use of a mechanical ventilator is carried out to overcome the acid-base balance disorder. Nurses as part of the Healthcare team have a role in early detection, critical thinking, providing interventions and coordinating for decision making. Conclusion. TBM infection with COVID-19 can cause a variety of signs and symptoms. Handling of patients requires good teamwork among health workers in early detection of clinical changes in patients. Keyword :Turbeculous Meningitis,COVID-19, Nursing